Efektivitas Media Tandem Spike Trainer Terhadap Akurasi Smash Pada Atlet Bola Voli Junior - Paulan Sukmadayani Pratiwi; Aam Ali Rahman; Dewi Susilawati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to examine the effectiveness of using a tandem spike trainer media in improving smash accuracy among junior volleyball athletes. The method used was a pre-experimental design with a One Group Pretest–Posttest Design. The sample consisted of 20 male junior volleyball athletes aged 10–15 years who actively trained at Tanjungsari Club, Sumedang Regency, selected using a purposive sampling technique. Data were collected through smash skill tests and interviews. Data analysis was conducted using normality tests, homogeneity tests, paired sample t-test, and coefficient of determination (R-square) analysis with the help of SPSS software. The results showed a significant improvement between pretest and posttest scores. In addition, athletes demonstrated positive responses, including increased motivation, self-confidence, and ease in performing repeated exercises with a stable ball position. In conclusion, the use of a tandem spike trainer is effective in improving the smash accuracy of junior volleyball athletes and can be used as an innovative training medium in athlete development programs.   Keywords: Accuracy, Smash, Tandem Spike Trainer, Volleyball